Empowering Smart Cities with AI and RPA: Strategies for Intelligent Urban Management and Sustainable Development - Venigandla, Kamala; Vemuri, Navya; Nnamere Aneke, Ezekiel (International Journal of Scientific Research and Management (IJSRM), 2024)
This research explores the transformative potential of Artificial Intelligence (AI) and Robotic Process Automation (RPA) in empowering smart cities to achieve intelligent urban management and sustainable development. Through a comprehensive analysis of literature, case studies, and qualitative research methods, the paper identifies key strategies for leveraging AI and RPA to address urban challenges and promote sustainable urban development. The integration of AI and RPA technologies enables data-driven decision-making processes, streamlines administrative workflows, and enhances service delivery in smart cities. Furthermore, AI and RPA contribute to promoting sustainable development goals by optimizing resource utilization, improving environmental management practices, and enhancing resilience to climate change. However, the widespread adoption of AI and RPA in smart cities faces challenges related to privacy, data security, and equity, which must be carefully addressed to ensure responsible and equitable deployment of these technologies. By adopting comprehensive strategies, fostering collaboration between stakeholders, and embracing a culture of innovation, cities can harness the full potential of AI and RPA to build smarter, more resilient, and sustainable urban environments for all residents. This research provides valuable insights for policymakers, urban planners, and technology providers seeking to leverage AI and RPA to address urban challenges and promote sustainable development in smart cities.